ANALYSIS OF FLIGHT INFORMATION CENTER SERVICES TOWARD TRAFFIC THAT DOES NOT DO TWO-WAY COMMUNICATION IN THE JAYAPURA SECTOR'S FIC UJUNG PANDANG AREA - Naufal, Hilmi; Ratna Sari, Dewi; Rochmawati, Laila (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Ujung Pandang FIC Jayapura Sector is a Flight Information Services unit in class G airspace, serving various kinds of domestic, military and overflying flights. in carrying out their duties, the Aeronautical Communication Officer (ACO) must, of course, serve every aircraft in their territory from the time the aircraft enters its territory until the aircraft leaves its territory. In its service, there are many obstacles such as aircraft entering the airspace of Ujung Pandang FIC Jayapura Sector without carrying out two-way communication or two-way communication, of course this can have an impact and endanger flight safety. This study uses mixed methods, researchers combine quantitative and qualitative data to find out how well the services provided and the causes of not carrying out two-way communication by pilots operating at the Ujung Pandang FIC Jayapura Sector unit. The purpose of this research is to find out the causes and obstacles experienced by aircraft that do not make contact with the Ujung Pandang FIC Jayapura Sector unit. The research was conducted on 30 Aeronautical Communication Officers (ACO) and 3 pilots from different airlines operating in the Ujung Pandang area of FIC Jayapura Sector. The results of the study show that the services provided by the Ujung Pandang FIC Jayapura Sector unit are in accordance with the Standard Operational Procedure (SOP) and can be said to provide very good service. On the other hand, interviews conducted with the three pilots showed that the pilots still had difficulty making contact/two-way communication with the Ujung Pandang FIC Jayapura Sector unit so that it could be seen that the cause of the aircraft not making contact/two-way communication was due to limited facilities and telecommunications networks that did not yet reach throughout the Ujung Pandang area of FIC Jayapura Sector.